Peran Regulasi Dan Kebijakan Pemerintah Dalam Implementasi Pajak Karbon Dan Pajak Hijau Di Indonesia - Al Kautsar, Gathan Alif; Bandiyono, Agus (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
Abstract: This paper discusses the role of government regulations and policies in implementing carbon taxes and green taxes in Indonesia. With increasing global attention to climate change and environmental sustainability, Indonesia faces the challenge of reducing carbon emissions and supporting environmentally friendly practices through effective fiscal instruments. Carbon taxes and green taxes are two important tools that can be used to achieve this goal. This study explores the existing legal and policy framework, analyzes the potential impact of implementing these taxes, and identifies the obstacles and opportunities faced in the implementation process. The research results show that clear regulations and consistent policies are essential for the successful implementation of carbon taxes and green taxes. In addition, support from various stakeholders, including the private sector and civil society, is needed to ensure the effectiveness and sustainability of this policy. In conclusion, this paper provides strategic recommendations for the Indonesian government to strengthen regulations and policies to support the transition to a low-carbon and green economy. Keywords: regulations, government policy, carbon tax, green tax, carbon emissions, environmental sustainability.